The Effect of Cytoflavin on the Outcome of Ischemic Stroke in Children - Ya. N. Majidova; A. E. Khalilova (Антибиотики и Химиотерапия, 2020)
The aim of the study is to assess the impact of cytoflavin inclusion on the dynamics of indicators of arterial ischemic stroke of various etiologies in children. Dynamic monitoring of 47 children with arterial ischemic stroke was carried out, 30 of them received cytoflavin via a slow intravenous drip infusion with 5 ml of the drug per 100 ml of saline for 10 days. Subsequently, after 2, 6 months and one year patients received the tablet form of the drug 2 times a day in the 1st year after the disease in the complex of rehabilitation measures, in the course of 25 days. The control group consisted of 17 patients who received only basic therapy. In addition to the conventional methods of assessment, transcranial ultrasound dopplerography and electroencephalogram were performed; patients were assessed using the pedNIHSS and PSOM-SNE scales. The severity of seizures was evaluated according to the NHS3 scale. The degree of impaired consciousness was evaluated using Glasgow Coma Scale. It was revealed that the inclusion of cytoflavin in neurometabolic correction in patients with arterial ischemic stroke positively affects the state of cerebral hemodynamics, which is confirmed by transcranial ultrasound dopplerography. The clinical effect of the inclusion of the drug in the treatment regimen is manifested by a decrease in sensorimotor and cognitive impairment, a reduced risk of epileptic activity foci forming as a result of a penumbra zone decrease, which ultimately increases the rehabilitation potential of children with ischemic stroke.